The role of gastroesophageal reflux disease in the middle ear pathology formation - Mikhail V. Komarov; Anastasiya A. Fedotova; Evgeniya V. Bezrukova (Наука и инновации в медицине, 2024)
The study of the extraesophageal reflux effect on the middle ear structures in adults is of considerable interest. The mechanism of formation of gastroesophageal reflux disease associated otitis media is closely related to such concepts as nasopharyngeal reflux and laryngopharyngeal reflux.